Race, gender and colonialism in Victorian representations of North Africa : the writings of Charlotte Bronte, Ouida and Grant Allen - Aimillia Mohd Ramli (Faculty of Humanities, University of Manchester, 2008)
Charlotte Bronte, Ouida and Grant Allen are known for their novels that engage with the issue of gender, race and Empire within the context of nineteenth-century representations of French-colonised North Africa and Algeria. An analysis of colonial discourse, engaging specifically with Edward Said's Orientalism, is helpful in understanding the underlying anxieties and ambivalences regarding these issues that are present in these writers' works, and in particular Bronte's Villette. Ouida's Under Two Flags and Allen's The Tents of Shem. Not only do the novels provide a chronological analysis of the gradual transformations underwent by representations of Arabs in English literature from their portrait as courageous freedom fighters, in the middle of the nineteenth century, to a mass of blood-thirsty savages less than fifty years later, they also demonstrate shifts in the types of anxieties that colonial discourse underwent during this period: from fears regarding possible contaminative effect that the East was said to assert on the treatment of women in the West in Bronte's novel, through a more ambivalent attitude towards sexual practices in the region in Ouida's work and, finally, the tension that results from racial encounters and the fear surrounding degeneration in Britain in Allen's novel. While novels by Bronte and Ouida imply the sources of these anxieties as coming from outside Britain, Allen's writings reflect his fear that the future of the English race was being threatened by a surplus of childless and unmarried women within the metropolitan centre. In fact, the narratives studied here deeply imbricate the race and character of the English with gendered representations of North Africans during that period. Even though colonialism is perceived as consolidating the superiority of the English race in comparison to other races, increasing encounters between it and these 'others' at the periphery, in particular North Africa, inevitably expose anxieties to be a significant part of the English colonial identity.